The princess fugitive eaudiobook A reimagining of little red riding hood. - Melanie Cellier (Four Kingdoms, 2020)
Princess Ava used to be a weapon—sharp, strong and beautiful. But when she fails at her most important task, she's forced to flee from her own family. Only her personal bodyguard, Hans, remains loyal. Hans claims to know the real Ava but she finds that hard to believe—after all, she's been the villain so long that she can't remember anything else. Deep in exile, Ava learns her kingdom needs a hero, and she might be the only one who can save it. The catch? She'll have to ally herself with the people she blames for her downfall. But in a game of life and death where the stakes are an entire kingdom, winning over her enemies will only be the beginning. Can one fugitive save her people, her kingdom and—hardest of all—herself? In this reimagining of the classic fairy tale, Little Red Riding Hood , the girl in the red hood has been swallowed up by the wolf and must decide if she's willing to fight for her freedom, no matter the cost.